Improving quality of life with mind-body-spirit therapy (Islamic concepts) in chronic renal failure patients with hemodialysis - Ns. Errick Endra Cita; Dian Miftahul Mizan (International Journal of Health Science and Technology, 2019)
The number of new chronic renal failure patients with hemodialysis therapy continues to increase from year to year in Indonesia. The number of new patients by 2015 is 21050 patients and the number of active patients is 30554 from 249 units of hemodialysis. The quality of life of hemodialysis patients has decreased in physical, psychological, social and environmental dimensions. Mind-body-spirit therapy (Concepts of Islam) focuses on the ability to manage the mindset and psychic that will affect the physical, attitudes and behavior of individuals in addressing their lives. Giving mind-body-spirit therapy to hemodialysis patients to improve quality of life, given for 4 weeks with the frequency twice a week. Pre- experimental study with one group pre-test post-test. The sample of 23 patients with hemodialysis therapy taken by purposive sampling. The WHOQOL-BREF questionnaire was used in this study. Early screening on quality of life was taken in 23 patients (13 men and 10 women, mean age 51.5 years). Mind-body-spirit therapy (Islamic concept) consisted of Tausiyah (cognitive reconstruction), prayer, dhikr and drinking zam-zam water. The quality of life score was evaluated at week 5 after 4 weeks of treatments. All four dimensions of quality of life and quality of life were generally analyzed using Wilcoxon with significant results p 0.05. After the treatments, there is an increase in the quality of life in the physical, psychological, social, environmental, and general quality of life in hemodialysis patients. A mind-body-spirit therapy of 4 weeks is effective for improving the quality of life of patients with chronic renal failure with hemodialysis therapy.